Comprehensive Analysis of the Role of Heat Shock Proteins in the Immune Microenvironment and Clinical Significance of Hepatocellular Carcinoma - Xiao H; Wang B; Xiong S; Li C; Ding Y; Chao D; Mei B; Shen N; Luo G (Journal of Hepatocellular Carcinoma)
Han Xiao,1,2,* Ben Wang,3,* Shaomin Xiong,1,2,* Chunbo Li,3 Yanbao Ding,1,2 Dai Chao,1,2 Baohua Mei,1,2 Naiying Shen,3 Gang Luo1,2 1Department of Hepato-Biliary-Pancreatic Surgery, The First Hospital of Jiujiang City, Jiujiang, Jiangxi Province, 332000, People’s Republic of China; 2Jiujiang City Key Laboratory of Cell Therapy, The First Hospital of Jiujiang City, Jiujiang, Jiangxi Province, 332000, People’s Republic of China; 3Department of General Surgery, No. 215 hospital of Shaanxi Nuclear Industry, Xianyang, Shannxi Province, 712000, People’s Republic of China*These authors contributed equally to this workCorrespondence: Naiying Shen, Department of General Surgery, No. 215 hospital of Shaanxi Nuclear Industry, Xianyang, Shannxi Province, 712000, People’s Republic of China, Email 250164285@qq.com Gang Luo, Department of Hepato-Biliary-Pancreatic Surgery, Jiujiang First People’s Hospital, Jiujiang, Jiangxi Province, 332000, People’s Republic of China, Email luogangxueshu@163.comPurpose: Hepatocellular carcinoma (HCC) is a prevalent malignancy that not only imposes a substantial financial burden but also significantly impacts the quality of life and overall survival of affected individuals. Heat shock proteins (HSPs) are a protein class with significant involvement in safeguarding and restoring cellular integrity. They help restore proper protein structure by binding to and refolding denatured proteins. However, the specific role of HSPs in HCC requires further investigation.Methods: We analyzed the genomic characteristics of HSPs in liver cancer in the TCGA and ICGC databases, and functional enriched analysis of HSPs. Construction of an HSPs-Related Prognostic Model for patients with hepatocellular carcinoma. HSP-related risk score (HRRS) was identified as an independent prognostic factor in patients with hepatocellular carcinoma, and the clinical pathological characteristics and immune microenvironment of high-risk and low-risk groups were compared. Further, we studied HRRS-based liver cancer treatment strategies and confirmed the protein expression of HSPD1 and DNAJC5 in normal liver tissues and hepatocellular carcinoma tissues by collecting human hepatocellular carcinoma tissues.Results: We observed elevated expression levels of most HSPs across HCC tissues. In addition, 14 hSPs were found to be related to prognostic significance among HCC patients and utilized to develop HRRS prognostic model for prognosis prediction and risk stratification. The prognostic and immunotherapeutic response predictive value of HRRS was validated utilizing data from TCGA and GEO cohorts. Moreover, we created a nomogram to assess HRRS clinical utility and verified its efficiency through various methods. Through IHC was found that HSPD1 and DNAJC5 were significantly overexpressed in hepatocellular carcinoma tissues.Conclusion: Our results lead us to conclude that HCC’s development and progression are intimately associated with HSPs, and the HRRS model represents a potentially robust prognostic model that could assist in clinical decision-making regarding chemotherapy and immunotherapy for HCC patients. Moreover, HSPD1 and DNAJC5 have the potential to serve as therapeutic targets for HCC.Keywords: heat shock proteins, hepatocellular carcinoma, bioinformatics